Kinetic investigations on homo- and co-polymerizations of pentafluorophenyl (meth)acrylates. (15th January 2021) - Alex, Julien; Ulbrich, Jens; Rosales-Guzmán, Miguel; Weber, Christine; Schubert, Ulrich S.; Guerrero-Sanchez, Carlos
Graphical abstract: Highlights: Kinetics of RAFT (co)polymerization of pentafluorophenyl (meth)acrylate are reported. An automated parallel synthesizer facilitated the generation of experimental data. Control using a dithiobenzoate for acrylate polymerization depended on the solvent. Control for methacrylate copolymerizations depended on initial comonomer composition. Abstract: Pentafluorophenyl methacrylate (PFPMA) and pentafluorophenyl acrylate (PFPA) are frequently used monomers to produce advanced materials for biomedical applications via (co)polymerization reactions. This contribution reports kinetic investigations of the reversible addition fragmentation chain transfer (RAFT) copolymerization of PFPMA and methyl methacrylate (MMA) mediated by a dithiobenzoate chain transfer agent (CTA) at 70 °C in dimethyl formamide (DMF). Control with respect to the molar mass of the copolymers was observed for initial PFPMA monomer feeds ≤40 mol%. The rate of PFPMA incorporation decreased with increasing initial PFPMA feed ratios. Reactivity ratios were estimated with a nonlinear regression that utilizes a visualization of the sum of squares space method (rPFPMA  = 1.06 and rMMA  = 0.44). The slight preference for MMA-type radicals to add PFPMA monomers increased the rate of consumption of PFPMA especially in low initial PFPMA monomer feeds. In addition, kinetic investigations of the RAFT homopolymerization of PFPA revealed an induction period and poor control on the polymer molar mass in the polar solvents acetonitrile and DMF using a dithiobenzoate CTA. A better control using the same CTA was observed in 1, 4-dioxane. Polymerizations carried out in the presence of a trithiocarbonate CTA were less affected by the solvent polarity and a good control on the polymer molar mass was achieved in acetonitrile and 1, 4-dioxane even at high monomer conversion (>95%, dispersity value ( Ð ) ≤ 1.19).